Large-scan-area sub-terahertz imaging system for nondestructive food quality inspection. (February 2019) - Ok, Gyeongsik; Shin, Hee Jun; Lim, Min-Cheol; Choi, Sung-Wook
Abstract: A subwavelength transmission imaging system based on Bessel–Gauss beam focusing in the 140 GHz frequency band (λ = 2.14 mm) was constructed for food quality inspection purposes. The system employed a low-cost beam source for imaging via mechanical raster scanning, and the high resolution (0.75 λ) focusing module had an extended depth of focus (12.6 λ) and supported a large scan area (800 × 400 mm 2, 30 min scan time). The performance of the proof-of-concept system was nondestructively investigated by using a variety of food products, such as chocolate bars, dried laver, red ginseng, and walnuts. Highlights: Subwavelength transmission imaging was implemented for food quality inspection. Large area inspection was demonstrated with a low-cost millimeter wave source. Various food products were nondestructively tested with high resolution and long DOF.